Numerical characterization of transient polarization square-wave switching in two orthogonally coupled VCSELs - Torre, Maria Susana (2011)
We study the dynamics of two vertical-cavity surface-emittinglasers (VCSELs) mutually coupled such that the natural lasing polarizationof each laser is rotated by 90 degrees and then is injected into the otherlaser. Simulations based on the spin-flip model show transient square-wavepolarization switchings before a stationary state is reached. The influenceof various model parameters on the duration of the stochastic transient timeand on the lasers’ dynamics in the stationary state is investigated.